Optimization of Zakat Management in Baznas on Community Empowerment in Parepare City - Rifdaningsi, Rifdaningsi; Yunus, Mukhtar (IAIN Parepare, 2020)
This study aimed to find out how to optimize zakat management at BAZNAS towards community empowerment in Parepare city. This research used theological approach, phenomenological approach, and juridical approach, The source of this research data came from primary legal materials and secondary legal materials. This research was classified as qualitative, using data in the form of direct interviews and documents. The data obtained then collected both primary and secondary. Data collection techniques ware carried out through observation, interviews, and documentation studies in order to obtain clear and representative data, while data processing and analysis techniques ware carried out through data reduction, data presentation and made conclusions. The results of this study indicated that Its distribution was still traditional and productive creative and it was not in accordance with the principles of justice. In terms of utilization of community empowerment has not optimal yet because it did not go through stages of capacity building and assistance.